Peran Pemuda Kalimantan Tengah Menyambut Ibu Kota Negara Nusantara - Panjika, Yunus Praja; Rahman, Rahman; Griando, Febriomico; Sjahputra, Hafidz Ridha Try (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Discussion public discussion with the theme “The Role of Central Kalimantan Youth in Welcoming the Capital City of the Archipelago” was held on February 26, 2025, at the Hall of the Youth and Sports Service of Central Kalimantan Province. Sports of Central Kalimantan Province. This event aims to increase awareness, increase capacity, and strengthen collaboration between the younger generation and various stakeholders to prepare for the future. and various stakeholders to prepare for the upcoming changes. coming. This discussion serves as a platform for young people to engage in dialog, share ideas and formulate strategies to in dialog, share ideas, and formulate strategies to overcome challenges and seize opportunities. and capitalize on opportunities. The establishment of Nusantara will have a to Central Kalimantan in terms of infrastructure, economy, society, and culture. This public discussion is expected to produce recommendations policy recommendations and practical strategies for local governments, educational institutions, youth communities, and the private sector in responding to the development of Nusantara. By encouraging innovation and collaboration, the young generation of Central Kalimantan can transition from mere spectators to active contributors to sustainable and inclusive development. sustainable and inclusive development.